2014
DOI: 10.1128/genomea.00191-14
|View full text |Cite
|
Sign up to set email alerts
|

Full Genome Analysis of Influenza A(H1N1)pdm09 Virus Isolated from Peru, 2013

Abstract: The pandemic influenza A(H1N1)pdm09 virus has been reported in Peru since 2009. We report the whole-genome sequence analysis of a viral isolate from an infection case that occurred during an influenza outbreak in 2013. This strain shows novel hemagglutinin (HA) mutations that may cause an antigenic drift that diminishes the protective effect of the vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…This transient mutation, also called an ''adaptive mutation'', may be the consequence of individual mutations that relieve the selective pressure caused by survival [11]. The K180Q mutation was (at least, in the Beijing area) a novel substitution within the Sa antigenic site of the H1 segment; this mutation has also been observed in Peru and India since 2013 [9,26]. In H3, three amino acid mutations were detected at two antigenic sites (A and B); these substitutions were observed in 2012-2013, but at a lower frequency [10].…”
Section: Discussionmentioning
confidence: 93%
“…This transient mutation, also called an ''adaptive mutation'', may be the consequence of individual mutations that relieve the selective pressure caused by survival [11]. The K180Q mutation was (at least, in the Beijing area) a novel substitution within the Sa antigenic site of the H1 segment; this mutation has also been observed in Peru and India since 2013 [9,26]. In H3, three amino acid mutations were detected at two antigenic sites (A and B); these substitutions were observed in 2012-2013, but at a lower frequency [10].…”
Section: Discussionmentioning
confidence: 93%
“…This mutant was first described in isolates from Peru, and our analysis showed that its location within the antigenic site Sa could allow the virus to escape from the immune response elicited by current vaccines. 22 Moreover, this change has been described in escape mutants of the HA from 1918. 23 Interestingly, despite that mutant S188T is located in antigenic site Sb and has become prevalent since 2009, 24 it appears to have had little impact in antigenic drift because no evidence has been reported to date of reduced vaccine efficacy caused by this mutant.…”
Section: Discussionmentioning
confidence: 95%
“…Also, HRM analysis for characterization of influenza subtypes [18, 25-27] and resistance isolates were reported [10-12,[28-31]. In this study, HRM analysis allowed us to analyze a larger number of samples compared to similar previous studies [32-33], which allowed us to obtain more robust data on the distribution of the most frequent genotypes circulating in Peru. Likewise, our results can be used to monitor changes in the distribution of influenza A(H1N1)pdm09 genotypes over time, like that reported in other studies [7-8,[19-22].…”
Section: Resultsmentioning
confidence: 90%